Social Media Skill in Public Relations and Customer Service for Employers - Arifah Hidayati; Elfitra Desy Surya; Abdul Samad Arief; Achmad Daengs GS; Jose Marco G. Reyes (Nyimak: Journal of Communication, 2022)
Public relation is an important part of marketing activities that involves assessing or perceiving the general public’s attitudes and views, as well as general and specific consumers (segments), toward a company’s or product’s activities and brand policies, and then carrying out the necessary activities to create a positive image. This goal can be achieved by using suitable media to complete customer satisfaction so that skills in utilizing social media are the main thing that public relations must do. This study aims to determine the ability to use social media by entrepreneurs such as university graduates when they start working. This study uses a quantitative approach with a survey method. The population in this study is Indonesian entrepreneurs. A survey of 396 entrepreneurs was chosen as the method. The findings show that public relations and customer service are the most sought-after social media skills among university graduates, ahead of knowledge of social media content creation, strategy development, and analytics.Keywords: Social media skill, public relations, customer service, employersABSTRAKHumas adalah bagian penting dari kegiatan pemasaran yang melibatkan penilaian atau persepsi sikap dan pandangan masyarakat umum, serta konsumen (segmen) umum dan khusus, terhadap kegiatan perusahaan atau produk dan kebijakan merek, dan kemudian melakukan kegiatan yang diperlukan untuk menciptakan citra positif. Tujuan tersebut dapat dicapai dengan menggunakan media yang sesuai untuk melengkapi kepuasan pelanggan sehingga keterampilan dalam memanfaatkan media sosial menjadi hal utama yang harus dilakukan oleh humas. Penelitian ini bertujuan untuk mengetahui kemampuan penggunaan media sosial oleh para pengusaha seperti lulusan universitas ketika mereka mulai bekerja. Penelitian ini menggunakan pendekatan kuantitatif dengan metode survei. Populasi dalam penelitian ini adalah pengusaha Indonesia. Sebuah survei terhadap 396 pengusaha dipilih sebagai metode. Temuan menunjukkan bahwa hubungan masyarakat dan layanan pelanggan adalah keterampilan media sosial yang paling dicari di kalangan lulusan universitas, di atas pengetahuan tentang pembuatan konten media sosial, pengembangan strategi, dan analitik.Kata Kunci: Keterampilan media sosial, hubungan masyarakat, pelayanan pelanggan, pengusaha